Undocumented identity storytelling: (Re)framing public relations. (1st March 2017) - Ortiz Juarez-Paz, Anna V.
The Undocumented Student Movement (USM) consists of members of a historically misrepresented and excluded population in the United States. Taking matters into their own hands, they have gained a voice in mainstream media and society today. In this article, I seek to document the communicative acts of resistance employed by undocumented students in the United States. Specifically, I argue that the communicative acts currently employed by the USM answer the call for a more critical and engaged theory of public relations. The USM offers alternative ways to communicate with publics through the use of undocumented identity storytelling. By employing the culture-centred approach to communication, I examine undocumented identity storytelling through participant observation and in-depth interviews with members of the movement.